Presentation - González-Becerril, Juan Gabino (Papeles de Población, 2017)
Sudies on Mexico-U.S. international migration as well as its interpretations have changed over time. At present, they focus on deportations in the context of the recent political transition in the United States. Some authors express their concern due to the dramatic disintegration of the migratory system in the United States, owing to the increasing deportation of illegal immigrants (those who are considered the unwanted), as of early 2000 this opened the road for increasingly restrictive migratory laws. The disintegration or separation between deported migrants and their families have a long history, which has varied over time, in Mexico, in the early XX century, the concern was the 1929 economic crisis. Such period was known as the era of hitching, conversely between 1929 and 1941, owing to its numbers, it was called the era of deportations.